Influence of job environment on the online teaching anxiety of college teachers in the online teaching context: The mediating role of subjective well-being - Zhang, Xu; Li, Suqi; Wang, Shuwen; Xu, Jinlei (Frontiers in Public Health, 2022)
Background Online education has been conducted widely in higher education in recent years. While online teaching brings many opportunities, it also poses numerous challenges and issues. This is especially true for college teachers, for whom teaching is considered to be a profession with a high level of burnout and anxiety. The large-scale application of online teaching methods has put teachers in an even more challenging context, which may lead to teaching anxiety affecting their mental health. In online teaching contexts, the question of what factors affect college teachers' online teaching anxiety is worth exploring to help reduce their online teaching anxiety so as to promote their work performance. In this study, therefore, we conducted a survey of college teachers to develop a model of job environment (job demands and job resources), subjective well-being, and online teaching anxiety, and to explore the influences of job environment and subjective well-being on their online teaching anxiety, as well as the mediating effects of subjective well-being between job environments and online teaching anxiety. Method Of the 1,060 college teachers who participated, 524 were male (49.4%) and 536 were female (50.6%). An online questionnaire was sent to the teachers in January, 2022. Online teaching anxiety, subjective well-being, and job environment scales were adapted and developed. Descriptive analysis, reliability and validity analysis, and structural equation modelling were used to analyse the collected data. Results The study model showed an adequate fit (χ2 = 440.983, RMSEA = 0.070, GFI = 0.942, AGFI = 0.914, NFI = 0.949, and CFI = 0.956), confirming the relationships of job demands and online teaching anxiety (β = 0.310, p < 0.001), job resources and online teaching anxiety (β = – 0.086, p < 0.01), job demands and subjective well-being (β = – 0.411, p < 0.001), job resources and subjective well-being (β = 0.204, p < 0.001), and subjective well-being and online teaching anxiety (β = – 0.435, p < 0.001). Meanwhile, the results also proved the effects of the mediating role of subjective well-being between job demands (95% CI = [– 0.138, – 0.225]), job resources (95% CI = [– 0.119, – 0.064]), and online teaching anxiety. The model accounted for 33.8% (f2 = 0.401) of online teaching anxiety. Conclusion The results of this study indicated that it is important to reduce job demands and increase job resources to alleviate college teachers' online teaching anxiety to maintain good mental health; while maintaining a high level of college teachers' subjective well-being is also helpful for promoting their work performance. Furthermore, the indirect effects of job demands and job resources on online teaching anxiety mediated by college teachers' subjective well-being were also significant.